Reflections on teaching an engineering course through murder mysteries - Krishna Kumar (OmniaScience, 2023)
This paper presents a reflective analysis of a novel approach to Problem-Based Learning (PBL) to teach abstract concepts in a large-class setting, specifically tailored for a third-year required undergraduate course, "Introduction to Geotechnical Engineering." The primary objective is to enhance student engagement and learning outcomes by employing forensic case studies-based learning, also known as murder mysteries. This unique adaptation of PBL offers a fresh perspective on teaching abstract concepts by introducing real-world engineering failures relevant to the topic. Students then identify potential reasons for failure, rank them, and cooperatively explore them. By progressing from the known to the unknown, students develop a comprehensive understanding of the fundamental principles they later encounter. by progressing from the known to the unknown This approach overcomes the limitations of traditional teaching methods that introduce abstract concepts before presenting real-world examples. The murder mysteries capture students' attention and interest, allowing them to experience the process of doing real-world engineering. Consequently, the course rating improved significantly, achieving the highest score in the last twenty years - 4.9 out of 5.0, well above the average course rating of 3.8 during the same period. The paper delves into the background, methodology, challenges, and reflections on implementing and evaluating this engaging and effective PBL adaptation in a large-class setting for teaching abstract concepts in engineering.